Mathematical models: a precious tool for research in physiology - Lascano, Elena Catalina (2015)
The use of mathematical models in science has increased in the last decades, since it is clear that they constitute an essential tool for the progress of experimental research. The main goal of this review is to present to the experimental physiologists some background on the different steps that are usually followed to develop a model. Probably more important, we aim to provide some basic thoughts to highlight the importance and need of mathematical modeling for scientific discovery and progress. The review also recapitulates the evolution of myocyte and Ca²⁺ handling models, the parallel work done in the interpretation of cardiac force generation, the integration of myocyte and force models into mechano-electric representations, and the construction of multi-scale models by assembling ventricular models with the mathematical descriptions of the circulatory system.